2003
DOI: 10.1038/nsb891
|View full text |Cite
|
Sign up to set email alerts
|

Coat protein fold and maturation transition of bacteriophage P22 seen at subnanometer resolutions

Abstract: Bacteriophage P22 is a prototypical biological machine used for studying protein complex assembly and capsid maturation. Using cryo-EM, we solved the structures of P22 before and after the capsid maturation at 8.5 A and 9.5 A resolutions, respectively. These structures allowed visualization of alpha-helices and beta-sheets from which the capsid protein fold is derived. The capsid fold is similar to that of the coat protein of HK97 bacteriophage. The cryo-EM shows that a large conformational change of the P22 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
201
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(214 citation statements)
references
References 26 publications
13
201
0
Order By: Relevance
“…The capsid protein is organized into a T ¼ 4 icosahedral lattice and has a HK97 fold. This fold of the capsid protein has been observed in all tailed phages (12)(13)(14)(15)(16)(17)(18). The short C1 tail is surrounded by a skirt of 12 long appendages, each terminating with a flexible globular domain, unlike those of tailed phages studied previously.…”
mentioning
confidence: 73%
“…The capsid protein is organized into a T ¼ 4 icosahedral lattice and has a HK97 fold. This fold of the capsid protein has been observed in all tailed phages (12)(13)(14)(15)(16)(17)(18). The short C1 tail is surrounded by a skirt of 12 long appendages, each terminating with a flexible globular domain, unlike those of tailed phages studied previously.…”
mentioning
confidence: 73%
“…The fold of these secondary structural elements is reminiscent of a canonical fold first identified in the HK97 head protein gp5 (Fig. 3C) (11) and, subsequently, found in the major capsid proteins of many DNA viruses, including epsilon15 (6, 7), P22 (12), and herpesvirus capsid (13). A BLAST search for BPP-1 protein homologs identified that Bbp17 has 35% sequence identify to HK97 gp5.…”
mentioning
confidence: 99%
“…Figure 4 shows the 3D structure of a HK97 subunit superimposed on a cryo-EM image of a P22 subunit. Jiang et al [7] have shown that the major helices of P22 undergo significant movement during the maturation transition as shown in figure 5. Whether the major helices of HK97 undergo a similar motion has not yet been unambiguously resolved [3].…”
Section: Analysis and Datamentioning
confidence: 99%
“…These processes were first studied with phages T4 and lambda using optical diffraction of negatively stained micrographs [6,13]. Subsequently, these processes have been studied at higher resolution by cryo-electron microscopy [1,7,9,10,12]. For phage P22, the hexagonal array of subunits at local six-fold axes are distinctively skewed, with a hole in the centre.…”
Section: Introductionmentioning
confidence: 99%